A bank-to-turn command calculation and singularity control strategy for agile missiles. (August 2014) - Wen, Qiu-Qiu; Xia, Qun-Li
This article proposes a new strategy that computes the bank-to-turn commands without a singularity problem. To this end, the singularity problem is first analysed, and the main influence factors are found. An extended roll-angle command calculation method is then derived for the missile body coordinate based on the bank-to-turn-90 logic. The auxiliary skid-to-turn manoeuvring and the command increment saturation are induced to eliminate the oscillation of roll-angle command due to the noises in guidance commands. Three control zones are designed to ensure that suitable command calculations are for different conditions. When the strategy is used, the missile tends to maintain a smooth and varied roll-angle command, even if the guidance acceleration commands approach zero at the endgame of guidance. Finally, numerical simulation results are provided, and the validity of the strategy is proven via a comparison between the typical bank-to-turn guidance law and the normal bank-to-turn command calculation method.